Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2174/1875399x010030100025
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Limb Coordinative Structure in a 200 m Front Crawl Event

Abstract: Abstract:The Index of Coordination has been currently used as a tool that measures the inter-arm lag time between propulsive phases in front crawl swimming. The aim of the present study was to assess the inter-arm coordinative structure during a 200m front crawl maximal effort, as well as to understand its interplay with the stroking parameters. One complete arm stroke cycle, without breathing, was digitized and analysed the relative duration of the different phases and identified the model of arm coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
3
4
1
1
Order By: Relevance
“…Only the duration of the pull phase had an increase over 200 m in this study (Table 1), confirming the hypothesis previously raised for this variable. These results differ from the findings by Figueiredo et al 4 , who found no intra-phase difference in the four sections of 200 m at maximum intensity. One explanation for this difference may be the speed at which the maximum test was performed in this study compared to the study of Figueiredo et al 4 : in the present study, the speed was, on average, 1.53 ms -1 , while in that study, 1.49 m.s -1 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Only the duration of the pull phase had an increase over 200 m in this study (Table 1), confirming the hypothesis previously raised for this variable. These results differ from the findings by Figueiredo et al 4 , who found no intra-phase difference in the four sections of 200 m at maximum intensity. One explanation for this difference may be the speed at which the maximum test was performed in this study compared to the study of Figueiredo et al 4 : in the present study, the speed was, on average, 1.53 ms -1 , while in that study, 1.49 m.s -1 .…”
Section: Discussioncontrasting
confidence: 99%
“…Similar behavior of SS was found for the 200 m front crawl among the 16 finalists of the 200 m freestyle race at the French national championship, among four high competitive level Portuguese swimmers and among six competitive Portuguese swimmers 4 , when SS presented decreased between the first 50 and the last 50 m of the race. The reduction in SL would be related to the inability to maintain the swimming technique, which would allow a larger distance traveled in each stroke cycle, on the other hand, an attempt to eliminate the effect of the reduced SL on the SS values would be to increase SR.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…IVV stability seems to be related with a coordinative adaptation of the upper limbs, as IdC changes along the effort, as well as the SR, mainly in the last 50 m lap [45, 46]. IVV ( x , y ) accounted for 15.2% of the variability of the 200 m swim and 13.2% for the 50 m laps.…”
Section: Discussionmentioning
confidence: 99%
“…O decréscimo conjunto da velocidade e da FG está de acordo com a literatura para nadadores com deficiência física unilateral de membro superior (12,13) . Estes estudos apresentam um aumento da DC com a diminuição da velocidade e da FG, mas os protocolos utilizados não consideram as alterações mecânicas induzidas pela fadiga, como acontece em situação de competição, dado que utilizam um protocolo de velocidade incremental (8) . Complementarmente é válido salientar que, para velocidades elevadas, os nadadores com amputação unilateral de membro superior (classe S8 e S9) utilizam a FG para conseguirem aumentar a velocidade de nado (13) , devido à necessidade de compensarem a falta de segmentos propulsivos (17) .…”
Section: Methodsunclassified